Handbook of medical imaging processing and analysis - Bankman, I. N. (Isaac N.) (San Diego, CA : Academic Press, 2000)
In recent years, the remarkable advances in medical imaging instruments have increased their use considerably for diagnostics as well as planning and follow-up of treatment. Emerging from the fields of radiology, medical physics and engineering, medical imaging no longer simply deals with the technology and interpretation of radiographic images. The limitless possibilities presented by computer science and technology, coupled with engineering advances in signal processing, optics and nuclear medicine have created the vastly expanded field of medical imaging. The Handbook of Medical Imaging is the first comprehensive compilation of the concepts and techniques used to analyze and manipulate medical images after they have been generated or digitized. The Handbook is organized in six sections that relate to the main functions needed for processing: enhancement, segmentation, quantification, registration, visualization as well as compression storage and telemedicine. * Internationally renowned authors(Johns Hopkins, Harvard, UCLA, Yale, Columbia, UCSF) * Includes imaging and visualization * Contains over 60 pages of stunning, four-color images.
pt. I. Enhancement -- pt. II. Segmentation -- pt. III. Quantification -- pt. IV. Registration -- pt. V. Visualization -- pt. VI. Compression storage and communication.
Includes bibliographical references and index.
Keywords: Diagnostic imaging -- Digital techniques -- Handbooks, manuals, etc; Imaging systems in medicine -- Handbooks, manuals, etc; Diagnostic Imaging; Biomedical engineering; Image Interpretation, Computer-Assisted -- methods -- Handbooks; Image Processing, Computer-Assisted -- methods -- Handbooks; Biomedical Engineering -- Handbooks; Diagnostic Imaging -- methods -- Handbooks; Electronic books; Handbooks, manuals, etc